Penerapan Nilai Dan Norma Global Melalui Model Penta-Helix Dalam Respons Terhadap Bencana Non-Alam: Studi Kasus Tragedi Kanjuruhan Dalam Perspektif Hubungan Internasional - Auliya, Akmal (Jurnal sosial dan sains, 2025)
The Kanjuruhan tragedy on October 1, 2022, underscored the importance of managing non-natural disasters in the sports sector. This study aims to analyze the application of global values and norms, such as public safety, human rights, and accountability, through the penta-helix model, which involves government, academia, society, media, and private sectors. Using a qualitative approach, this research examines secondary data, including official reports, international regulations, and academic publications. The findings reveal that although global norms have been established, their implementation at the national level faces challenges such as a lack of coordination among stakeholders and weak regulatory enforcement. Moreover, this tragedy negatively impacted Indonesia's international reputation, particularly in sports diplomacy. This study recommends enhancing multi-stakeholder coordination and policy reforms that integrate global values to prevent similar tragedies in the future.